Husserl: this holds only if subjectivity is taken as a natural object; epoché and reduction de-naturalize it. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
Husserl: this holds only if subjectivity is taken as a natural object; epoché and reduction de-naturalize it.
iso-id: iso:argument:o8geE4CY; sha256: sha256:8e42dbaa7a5c7421bdc8ee57566b66eca76dcc655fb80ac9b1d674a2eebdda89